"I'm Not Teaching English, I'm Teaching Something Else!": How New Teachers Create Curriculum Under Mandates of Educational Reform. Issue 2 (4th March 2018) - Costigan, Arthur
Abstract : This study presents how beginning teachers create and teach an English Language Arts (ELA) curriculum in urban schools in the context of an educational reform movement driven by mandates such as Common Core State Standards (CCSS), high stakes tests, and prescribed curricula. They serve in schools with each using unique and individual curricula due to frequent administrative turnover and reorganization. Through the use of participants' classroom writings, interviews, and records of their classroom teaching, this study presents that the participants are neither teaching the content they wish, nor able to use pedagogies they see as effective. They experience confusion about the nature of the curricula imposed on them which differs significantly from their understanding of the ELA curriculum. The curricula they teach has little to do with either personal understandings of ELA, or how it is presented it in their educational coursework.